Budget Efficiency Strategy to Support Educational Quality at MAN 3 Tasikmalaya City - H. Soro , Suharyanto; Arman, Arief Aditya; Robi Abdulrohim , Muhammad Nur Rochmat (Global Education Journal, 2025)
This study aims to analyze budget efficiency strategies in supporting the quality of education at MAN 3 Tasikmalaya City using a descriptive qualitative approach through the collection methods of participatory observation, in-depth interviews, and documentation studies. The results of the study indicate that the implementation of budget efficiency strategies has been carried out through a systematic and participatory approach by involving the principal, teaching staff, education personnel, and the madrasah committee in a realistic budget planning process with allocation priorities on improving the quality of education (75% of the total budget), improving the welfare of educators and education personnel, and developing learning facilities and infrastructure. The impact of the implementation of budget efficiency strategies on the quality of learning shows significant results in creating a conducive learning environment, improving basic learning facilities, and developing more adaptive and resourceful educator competencies, although there is still a gap between ideal needs and the reality of the available budget. The conclusion of this study contributes significantly to the development of an effective and efficient educational financial management model, especially for Islamic educational institutions that face budget constraints but still have to maintain competitive educational quality, and can be a reference for the government in formulating educational financing policies that are more responsive to the needs of educational institutions at the operational level.